2002
DOI: 10.1038/nrn874
|View full text |Cite
|
Sign up to set email alerts
|

Proneural genes and the specification of neural cell types

Abstract: Certain morphological, physiological and molecular characteristics are shared by all neurons. However, despite these similarities, neurons constitute the most diverse cell population of any organism. Recently, considerable attention has been focused on identifying the molecular mechanisms that underlie this cellular diversity. Parallel studies in Drosophila and vertebrates have revealed that proneural genes are key regulators of neurogenesis, coordinating the acquisition of a generic neuronal fate and of speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

40
1,316
2
38

Year Published

2002
2002
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,373 publications
(1,396 citation statements)
references
References 158 publications
40
1,316
2
38
Order By: Relevance
“…The idea that the growth of a new cerebellar lobule is the result of adult neurogenesis was further supported by the expression patterns of Mash1 and Ngn2, markers specific for NPCs 46, 47. Mash1 is predominantly expressed at the tip of the growing lobule, overlapping with CB expression (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The idea that the growth of a new cerebellar lobule is the result of adult neurogenesis was further supported by the expression patterns of Mash1 and Ngn2, markers specific for NPCs 46, 47. Mash1 is predominantly expressed at the tip of the growing lobule, overlapping with CB expression (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The activity of Cath6 to inhibit neuronal differentiation was unexpected because all of the Atonal superfamily molecules thus far identified promote neuronal differentiation (Yan and Wang, 1998;Morrow et al, 1999;Perron et al, 1999;Tomita et al, 2000;Hutcheson and Vetter, 2001;Inoue et al, 2002) and act as transcriptional activators (Cabrera and Alonso, 1991;Johnson et al, 1992;Bertrand et al, 2002). We speculated that Cath6 might function as a transcriptional repressor to counteract the function of these Atonal family genes, although Cath6 did not display significant sequence similarities to known transcriptional repressors.…”
Section: Cath6 Functions As a Transcriptional Activatormentioning
confidence: 86%
“…3E). On the other hand, mutant Cath6 (Cath6 Dbasic) lacking the basic region of bHLH domain, which is required for its DNA-binding activity (Bertrand et al, 2002), did not decrease the ratio of Islet1-positive cells (Fig. 3E).…”
Section: Cath6 Inhibits Differentiation Of the Retinal Ganglion Cellsmentioning
confidence: 95%
“…During brain development, NEUROG2 has a specific spatiotemporal expression pattern, because it is exclusively detected in the ventricular zone and only during neurogenesis (Fig 5A) 25. It has been demonstrated that a negative feedback mechanism is essential for the correct transition between the inhibition of neurogenesis and the induction of early gliogenesis 26. Furthermore, the disruption of proneuronal gene activity, such as that of NEUROG2 , may result in loss of commitment in specific neural progenitor cells27 and the generation of ectopic neurons 28.…”
Section: Discussionmentioning
confidence: 99%